Changes in the mobile phase composition on a stepwise counter‐current chromatography elution for the isolation of flavonoids from Siparuna glycycarpa. Issue 14 (24th June 2013) - Costa, Fernanda das Neves; Garrard, Ian; da Silva, Antonio Jorge Ribeiro; Leitão, Gilda Guimarães
<x xml:space="preserve">Abstract</x> This paper describes the isolation of flavonoids and other aromatic compounds from an ethyl acetate extract of leaves of Siparuna glycycarpa using stepwise elution counter‐current chromatography (CCC). The elution profile yielded the following compounds: diglycosylated flavonoids, quercetin 3‐O‐rutinoside and quercetin 7‐O‐rutinoside, followed by monoglycosylated flavonoids, kaempferol‐3‐O‐β‐glucopyranoside, kaempferol‐3‐O‐β‐rhamnopiranoside, kaempferol‐3‐O‐β‐6′′(p‐coumaroyl) glucopyranoside, and quercetin‐3‐O‐β‐glucopyranoside, and then free phenolics, protocatechuic acid, and 2′, 6′‐dihydroxy‐4, 4′‐dimethoxydihydrochalcone, which shows that this type of elution covers a broader range of polarity than the traditional isocratic mode. This makes it more suitable to perform separations of mixtures containing large differences in hydrophobicity. A GC analysis of a blank CCC run was performed to determine if changes in the mobile phase composition affect the chromatographic process. Results showed a gradual variation of the composition of the mobile phase emerging after the step gradient, favoring the selectivity of the solvent system.